Rapid Ice‐Wedge Collapse and Permafrost Carbon Loss Triggered by Increased Snow Depth and Surface Runoff - Parmentier, Frans‐Jan W.; Nilsen, Lennart; Tømmervik, Hans; Meisel, Ove H.; Bröder, Lisa; Vonk, Jorien E.; Westermann, Sebastian; Semenchuk, Philipp R.; Cooper, Elisabeth J. (Geophysical research letters, 2024)
Thicker snow cover in permafrost areas causes deeper active layers and thaw subsidence, which alter local hydrology and may amplify the loss of soil carbon. However, the potential for changes in snow cover and surface runoff to mobilize permafrost carbon remains poorly quantified. In this study, we show that a snow fence experiment on High‐Arctic Svalbard inadvertently led to surface subsidence through warming, and extensive downstream erosion due to increased surface runoff. Within a decade of artificially raised snow depths, several ice wedges collapsed, forming a 50 m long and 1.5 m deep thermo‐erosion gully in the landscape. We estimate that 1.1–3.3 tons C may have eroded, and that the gully is a hotspot for processing of mobilized aquatic carbon. Our results show that interactions among snow, runoff and permafrost thaw form an important driver of soil carbon loss, highlighting the need for improved model representation. Plain Language Summary Snow cover is steadily disappearing as a result of climate change, but in areas that remain below 0°C we can still expect an increase in snow depth in the middle of winter. Since snow acts akin to a blanket, this warms the soil and accelerates the thaw of permafrost—thereby potentially contributing to carbon release from these frozen soils. Ice wedges, which are typical for permafrost landscapes, are particularly vulnerable to thaw because they hold a large amount of ice. When this ice melts, the surface sinks down, and soil carbon may be lost. In this study, we show how experimentally raised snow cover triggered the collapse of several ice wedges, not only through a warming effect of the snow but also due to an increase in the flow of water through the ice wedge network. As a result, we estimate that 1.1–3.3 tons of carbon were removed from this location, of which a portion could have entered the atmosphere as CO2. We emphasize the importance of studying the interactions among snow, runoff, and permafrost thaw to better understand how this may affect the release of greenhouse gases to the atmosphere. Key Points A decade of raised snow depths led to strong local thaw subsidence, while increased runoff triggered the downstream collapse of ice wedges The abrupt thaw process mobilized about 1.1–3.3 tons of soil organic carbon in total, and dissolved organic carbon was degraded in the thermo‐erosion gully Feedbacks linking changes in snow cover, surface drainage, and permafrost thaw are important drivers of thermokarst and soil carbon loss